Strategic planning for dairy cattle: Swot analysis applied to a property of a farmers’ association in Dracena, Sao Paulo state, Brazil - Sabbag, Omar Jorge; Costa, Sílvia Maria Almeida Lima (Interações, 2015)
The sector of milk production in Brazil is very heterogeneous (high-tech in large scale X family properties). This study aimed to develop a diagnostic as a basis for a strategic plan to face the challenges inherent in operating a dairy farm in property of a farmers’ association in Dracena, São Paulo/Brazil. It was observed that the association needs a more efficient guidance in the marketing, production and finance areas, not to compromise the search for new markets and continued growth in activity.